Collagen dysplasia (cutaneous asthenia) in a cat - Sequeira, Julio Lopes [UNESP]; Rocha, Noeme Sousa [UNESP]; Bandarra, E. P.; Figueiredo, LMA; Eugenio, F. R. (Amer Coll Vet Pathologist, 1999)
Hereditary collagen dysplasias comprise a complex group of connective-tissue disorders that result in the reduced tensile strength of affected tissues. These processes are called cutaneous asthenia in the skin of dogs and cats. We report here the case of a crossbred male cat, aged 6 months, that presented with two skin wounds in the region of the right thorax and right iliac tuberosity. The skin of these regions and of the animal's dorsum was hyperextensible, smooth to the touch, and easily torn with minor trauma. Microscopic examination of skin samples revealed reduced dermal connective tissue consisting of shortened and fragmented collagen fibers. Normal fibers were intermingled with altered fibers. Ultrastructural changes in collagen fibers included disorientation of fibrils within the same bundle, marked spacing differences, and variation in the diameter of transverse sections. The fibrils maintained the transverse striations characteristic of normal collagen.
Keywords: collagen disease; connective tissue; cutaneous asthenia; Ehlers-Danlos syndrome; felines